(untitled) (Journal of Hama University, 2026)
يهدف البحث الحالي إلى تعرّف دور منهج مونتسوري في تحسين التّفاعل الاجتماعيّ لدى أطفال الرّوضة من وجهة نظر المعلّمات، وتعرّف الفروق في متوسّطات إجابات أفراد العيّنة حول دور منهج مونتسوري في تحسين التّفاعل الاجتماعيّ لدى أطفال الرّوضة تبعاً لمتغيّريّ (المؤهّل العلميّ وسنوات الخبرة)، وقد اتّبعت الباحثة المنهج الوصفيّ التّحليليّ، حيث تمّ تطبيق البحث على عيّنة مقصودة من معلّمات رياض الأطفال التّي تطبّق منهج مونتسوري، بلغ عددها (49) معلّمة، واستخدمت الباحثة استبانة مؤلّفة من (20) بنداً كأداة لجمع المعلومات والبيانات، وقدّ توصّل البحث إلى النّتائج الآتيّة: - جاء دور منهج مونتسوري في تحسين التّفاعل الاجتماعيّ لدى أطفال الرّوضة بدرجة متوسّطة، إذ بلغت قيمة المتوسّط الحسابي (3.05). - عدم وجود فروق ذات دلالة إحصائيّة بين متوسّطات إجابات المعلّمات حول دور منهج مونتسوري في تحسين التّفاعل الاجتماعيّ لدى أطفال الرّوضة تبعاً لمتغيّر المؤهّل العلميّ. - وجود فروق ذات دلالة إحصائيّة بين متوسّطات إجابات المعلّمات حول دور منهج مونتسوري في تحسين التّفاعل الاجتماعيّ لدى أطفال الرّوضة تبعاً لمتغيّر سنوات الخبرة لصالح (10 سنوات فأكثّر). في ضوء النّتائج يقدّم البحث جملة من المقترحات أهمها: إقامة ندوات وورش عمل بإشراف إدارة الرّوضة لمعلّمات رياض الأطفال، الهدف منها توعّيتهنّ بأهمّية الدّور المحوريّ لمنهج مونتسوري في تنمّية المهارات الاجتماعيّة لدى الأطفال، ولا سيما التّفاعل الاجتماعيّ مثل: (الاستئذان من المعلّمة قبل الحديث، الالتزام بقواعد اللّعب مع الأقران، تجنّب مُقاطعة حديث الآخرين)، وضرورة إعداد برامج تدريبيّة متخصّصة لمعلّمات رياض الأطفال، لتدريبهنّ على الاستخدام الأمثل لأدوات مونتسوري التّعليميّة، وتصميم أنشطة تفاعليّة تعزّز التّواصل والتّعاون بين الأطفال The current research aims to identify the role of the Montessori curriculum in improving social interaction among Kindergarten Children from the teachers’ perspective, and to identify the differences in the average responses of sample members regarding the role of the Montessori curriculum in improving social interaction among Kindergarten Children according to the variables (academic qualification and years of experience). The researcher followed the descriptive analytical approach, where the research was applied to a deliberate sample of (49) Kindergarten teachers. The researcher used a questionnaire consisting of (20) items as a tool for collecting information and data. The research reached the following results: -The role of the Montessori curriculum in improving social interaction among Kindergarten Children was moderate, as the arithmetic mean value reached (3.05). -There are no statistically significant differences between the averages of teachers’ answers regarding the role of the Montessori method in improving social interaction among Kindergarten Children according to the educational qualification variable. - There are no statistically significant differences between the averages of teachers’ answers regarding the role of the Montessori method in improving social interaction among Kindergarten Children according to the years of experience variable in favour of (10 years or more). In light of the results, the research presents a set of proposals, the most important of which are: holding seminars and workshops under the supervision of the Kindergarten administration for Kindergarten teachers, with the aim of raising their awareness of the importance of the pivotal role of the Montessori approach in developing social skills in Children, especially social interaction such as: (asking permission form the teacher before speaking, adhering to the rules of playing with peers, avoiding interrupting others’ conversations), and the necessity of preparing specialized training programs for Kindergarten teachers, to train them on the optimal use of Montessori educational tools, and designing interactive activities that enhance communication and cooperation among children..